2016
DOI: 10.1007/s00216-016-9522-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid restriction enzyme free detection of DNA methyltransferase activity based on DNA-templated silver nanoclusters

Abstract: DNA methylation has significant roles in gene regulation. DNA methyltransferase (MTase) enzyme characterizes DNA methylation and also induces an aberrant methylation pattern that is related to many diseases, especially cancers. Thus, it is required to develop a method to detect the DNA MTase activity. In this study, we developed a new sensitive and reliable method for methyltransferase activity assay by employing DNA-templated silver nanoclusters (DNA/Ag NCs) without using restriction enzymes. The Ag NCs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The detection limit is calculated to be 2.01 Â 10 À3 U mL À1 by evaluating three times the standard deviation over the signal of negative control without M.SssI MTase. The sensitivity of this method has been improved by more than 497.5-fold compared with that of the colorimetric assay based on enzymelinkage-mediated AuNP aggregation (1.0 U mL À1 ), 18 164.2-fold compared with that of the electrochemical assay based on a photoelectrochemical (PEC) immunosensor (0.33 U mL À1 ), 51 49.8-fold compared with that of the luminescence assay based on DNA-templated silver nanoclusters (0.1 U mL À1 ), 52 and 29.9fold compared with that of the uorescence assay based on methylation-sensitive cleavage coupled with the nicking enzyme-assisted signal amplication (0.06 U mL À1 ), 30 and even is comparable to that of the uorescence assay based on SDA and DNAzyme amplication (0.0082 U mL À1 ). 53 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The detection limit is calculated to be 2.01 Â 10 À3 U mL À1 by evaluating three times the standard deviation over the signal of negative control without M.SssI MTase. The sensitivity of this method has been improved by more than 497.5-fold compared with that of the colorimetric assay based on enzymelinkage-mediated AuNP aggregation (1.0 U mL À1 ), 18 164.2-fold compared with that of the electrochemical assay based on a photoelectrochemical (PEC) immunosensor (0.33 U mL À1 ), 51 49.8-fold compared with that of the luminescence assay based on DNA-templated silver nanoclusters (0.1 U mL À1 ), 52 and 29.9fold compared with that of the uorescence assay based on methylation-sensitive cleavage coupled with the nicking enzyme-assisted signal amplication (0.06 U mL À1 ), 30 and even is comparable to that of the uorescence assay based on SDA and DNAzyme amplication (0.0082 U mL À1 ). 53 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugation of peroxidase mimic nanostructure with bio‐receptor not only decreased catalytic activity but also diminish binding affinity of bio‐receptor . Nowadays DNA has been attractive for its potency as a scaffold for synthesis of nanoclusters . This capacity resolved bio receptor conjugation in designing DNA biosensor.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies showed that exploiting the advantages of nanomaterials for biosensor fabrication while enhancing their performance improved their detection limit as demonstrated for DNA detection. [7][8][9][10] The conventional methods for the detection of MTase enzyme activity and methylated DNA include bisulte treatment, 11 high performance liquid chromatography (HPLC), 12 electrochemistry, [13][14][15][16][17] enzyme-linked immunosorbent assay (ELISA), 18 surface plasmon resonance (SPR) spectroscopy, 19,20 surface-enhanced Raman scattering (SERS), 21,22 and use of microuidic based biosensors 23,24 and uorescence based biosensors. [25][26][27][28] Although several attempts have been made for the detection of methylated DNA in recent years, there are still some drawbacks that limit their sensitivity and efficacy in clinical applications.…”
Section: Introductionmentioning
confidence: 99%